PANTON-VALENTINE LEUKOCIDIN-POSITIVE STAPHYLOCOCCUS AUREUS IN IRELAND 2002-2011: TWENTY-ONE CLONES, FREQUENT IMPORTATION OF CLONES, TEMPORAL SHIFTS OF PREDOMINANT METHICILLIN-RESISTANT S. AUREUS AND INCREASING MULTIRESISTANCE - TECKLENBORG, SARAH; COLEMAN, DAVID; SHORE, ANNA (My University, 2014)
There has been a worldwide increase in community-associated (CA) methicillin-resistant Staphylococcus aureus (MRSA) infections. CA-MRSA isolates commonly produce the Panton-Valentine leukocidin toxin encoded by the pvl genes lukF/S-PV. This study investigated the clinical and molecular epidemiology of pvl-positive MRSA and methicillin-susceptible S. aureus (MSSA) identified by the Irish National MRSA Reference Laboratory (NMRSARL) between 2002 and 2011. All pvl-positive MRSA (n = 190) and MSSA (n = 39) isolates underwent antibiogram-resistogram typing, spa typing and DNA microarray profiling for multilocus sequence type, clonal complex (CC) and/or sequence type (ST) and staphylococcal cassette chromosome mec type assignment and virulence and resistance gene detection. Where available, The prevalence of pvl-positive MRSA increased from 0.2%-8.8% and pvl-positive MSSA decreased from 20%-2.5% during the study period. The pvl-positive MRSA and MSSA belonged to 16 and five genotypes, respectively, with CC/ST8-MRSA-IV, CC/ST30-MRSA-IV, CC/ST80-MRSA-IV and CC1/ST772-MRSA-V and CC30-MSSA, CC22-MSSA and CC121-MSSA predominating. Temporal shifts in the predominant pvl-positive MRSA genotypes and a six-fold increase in multiresistant pvl-positive MRSA occurred during the study period. Analysis of patient data indicated that pvl-positive S. aureus strains, especially MRSA, were imported into Ireland several times. Two hospital and six family clusters of pvl-positive MRSA were identified and 70% of patient isolates for which information was available were from patients in the community. This study highlights the increased burden and changing molecular epidemiology of pvl-positive S. aureus in Ireland over the last decade and the contribution of international travel to the influx of genetically diverse pvl-positive S. aureus into Ireland.
PUBLISHED
26th Dec; Epub ahead of print
Keywords: Panton-Valentine leukocidin; MRSA; MSSA; multiresistance; community-associated; Immunology, Inflammation & Infection